Morphological and Molecular Diversity of Ginger (Zingiber officinale Roscoe) Pathogenic Fungi in Chilga District, North Gondar, Ethiopia - Tilahun, Sefinew; Alemu, Marye; Tsegaw, Mesfin; Berhane, Nega (Frontiers in Fungal Biology, 2022)
Ginger diseases caused by fungal pathogens have become one of the most serious problems causing reduced production around the world. It has also caused a major problem among farmers in different parts of Ethiopia resulting in a huge decline in rhizome yield. However, the exact causative agents of this disease have not been identified in the state. Although there are studies related to pathogenic fungus identification, molecular level identification of fungal pathogen was not done in the area. Therefore, the present study was undertaken to isolate and characterized the fungal causative agent of ginger disease from the diseased plant and the soil samples collected from Chilga district, Gondar, Ethiopia. Samples from infected ginger plants and the soil around the infected plant were collected. Culturing and purification of isolates was made using potato dextrose agar supplemented with antibacterial agent Chloramphenicol. The morphological characterization was done by structural identification of the isolates under the microscope using lactophenol cotton blue stains. Isolated fungi were cultured and molecular identification was done using an internal transcribed spacer of rDNA. A total of 15 fungal morphotypes including 10 Aspergillus spp (66.7%), 2 Penicillium spp (13.3%), a Metarhizium anisopliae strain and single uncultured fungus clone S23 were isolated from the samples representing all plant organs and the soil. Aspergillus spp. (66.7%) was the most common and seems to be the major causative agent. To our knowledge, this is the first report of ginger pathogen fungal in Ethiopia identified using (ITS rDNA) molecular techniques. This study will lay foundation for the development of management strategies for fungal diseases infecting ginger.